A Characterization of Compact SG Pseudo-differential Operators on L2(ℝn). (17th July 2014) - Damanik, David; Ruzhansky, Michael; Vougalter, Vitali; Wong, M.W.; Molahajloo, S.
<x content-type="archive" xml:space="preserve">Abstract</x> We give a necessary and sufficient condition for pseudo-differential operators with SG symbols to be compact from L2(ℝn) into L2(ℝn).